Influência da incorporação de vitamina C à dieta no desempenho produtivo de rãs-touro Lithobates catesbeianus pós-metamorfoseadas - Knoop, Rainer; Ferreira, Claudia Maris; Takahashi, Neuza S.; Franca, Fernanda Menezes; Antonucci, Antonio M.; Teixeira, Patricia C. [UNESP]; Sugohara, Atushi [UNESP]; Dias, Danielle De Carla [UNESP]; Tachibana, Leonardo; Hipolito, Marcio (Inst Pesca, 2011)
The experiment was developed in Marta Farm, Tremembe city, located in the State of São Paulo - Brazil, using a frogculture commercial project. The aim of this study was evaluate the performance (growth, survival and feed conversion) of bullfrogs Lithobates catesbeianus, post-metamorphosed fed with diets containing different amounts of vitamin C and your performance with the temperature. The animals were kept in 24 boxes of (2.0 x 1.0 m) with an initial density of 50 animals per square meter. We tested the following levels of supplementation in the diet: 0, 250, 500, 750, 1,000 and 2,000 mg vitamin C kg(-1) of diet. The experimental design was completely randomized with six treatments and four replicates. The parameters evaluated were: feed intake, weight gain, feed conversion and survival tax. The animals were weighed at the beginning of the experiment and every 30 days and recorded daily to room temperature. The percentage of food intake decreased with the growth of the frogs, from 3.85 to 1.2% of the live weight, and the mean of temperature decreased from 28 to 20.1 degrees C. It was concluded that there was no influence of vitamin C on the performance (growth, survival and feed conversion) of bullfrogs in the growing stage.
Influence of incorporation of vitamin C to the diet in the productive performance of bullfrog Lithobates catesbeianus post-metamorphosed
Keywords: Ascorbic acid; antioxidant; performance; animal stress; frogculture; supplementation